Here to Stay: Where the United States Stands in the International Competition for STEM Talent - Corrigan , Jack; Zwetsloot, Remco (International Higher Education, 2022)
Today, the United States is a top destination for international students pursuing doctoral degrees in STEM fields. Contrary to some claims, the vast majority of these students choose to stay in the United States after graduation. This ability to attract and retain top talent gives the United States a significant advantage. However, the country risks losing this edge if it fails to reform its immigration process to keep up with other countries.